The European Union in light of the COVID-19 Pandemic ‒ A Failure of European Integration or a Chance for Closer Cooperation among Member States? - Moskal, Anna; Sobarnia, Aleksandra; Pazera, Szymon; Kopania, Zuzanna (2021)
This publication discusses a diverse range of issues associated with European integration, ranging from the origins of the European Union, the evolution of the organisation over the last several decades, the changing visions of the future of Europe, the crises that the Member States faced in the past, and finally, the impact of the Covid-19 pandemic on the current and future level of European integration. Although the shape and future of the EU have been debated since its formation, the authors strongly believe that they need to be revisited due to the severe challenges this unique organisation and its Member States have been facing following the outbreak of COVID-19. The rapid spread of coronavirus around the world led to an unprecedented global emergency which severely affected many countries, including all the Member States of the EU. The COVID-19 pandemic put the ability of the EU to react quickly and effectively to the test. In addition, it also exposed the weak points of cooperation and solidarity of the Member States, and the level of trust their citizens have in the EU during a time of horrendous crisis. In this publication, a scope of integration and cooperation of the Member States is re-evaluated, and the level of European citizens’ trust given to the EU and its Member States during the deadly pandemic is analysed. In order to provide the reader with an in-depth and comprehensive research analysis on European integration, the study is presented through a historic, political, and legal lens.
Keywords: European integration; European Union; COVID-19 pandemic